Designing computer-based rewards with and for children with Autism Spectrum Disorder and/or Intellectual Disability - Constantin, Aurora; Johnson, Hilary; Smith, Elizabeth; Lengyel, Denise; Brosnan, Mark (Computers in human behavior, 2017)
Children with Autism Spectrum Disorder (ASD) tend to have an affinity for digital technologies, often preferring computer-assisted learning to human-assisted learning. Many children with ASD are also diagnosed with Intellectual Disabilities (ID), yet design studies involving children with ASD and ID are scarce. Rewards can have a positive impact on children's learning and motivation, but little is known about the nature and impact of rewards for children with ASD, and/or ID. Digital technologies are well placed to provide task-based rewards, and in combination with a better understanding of the reward preferences of children with ASD and/or ID this has significant potential to enhance learning. This paper presents two robust participatory design (PD) studies involving children with: i) ASD; ii) ID; and iii) both ASD and ID. The studies aimed to identify: i) the reward preferences of children with ASD and/or ID (RQ1) and ii) how rewards might develop throughout a task as the child progresses (RQ2). Results revealed a number of reward categories that were common to all children, as well as children's preferences for how rewards could develop as they progress through computer-based tasks, for the first time. Original implications for designing computer-based rewards embedded within digital intervention/educational technologies for children with ASD and/or ID, are discussed. •Children with ASD and/or ID appreciate rewards within digital educational platforms.•Reward topics are consistent across children groups.•There are individual differences in the specific instances of preferred rewards.•Children would like rewards that reflect their progression during tasks.•Children with ASD and/or ID can be included in the design research.